(3OjhGf UGdM GdJejejs - (3UGdM Hf OQhjT Hf Rjfj GdJejej,J (B1261 (3g` s ((3eMeO Hf WGgQ GdSeGhj s)
(3ChdgG (B:s
(3bGajI GdgeRI(B: (3bGd jeOM CejQ GdeDefjf Ydj Hf CHj WGdH Ydjg CaVd GdSdGe(B: (3ZGjI GdeOM aj YdGc EHJOGA djJ TYQj eG JUfY GdTYQGA s
(3BNQgG (B:s
(3ef MQa GdjGA(B: (3Ydjc ef GdQMef KqQJ SMGFH ef GdYah dG Jfac dWa LhGQjG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3LeY GdOjhGf hdO GdTGYQ cGXe Hf UGdMs
(3hoeQJH Ydi MQha GdgLGAs
(3hHChdg JQLeI ddeDdas
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs